The Role of Law in Managing the Tension between Risk and Innovation: Introduction to the Special Issue on Regulating New and Emerging Technologies. (September 2016) - Weimer, Maria; Marin, Luisa
Abstract : Technological innovations are crucial drivers of economic, social, and environmental progress. While innovations lead the evolution of our societies and permeate all domains of human life, they also pose significant risks both to humans and the environment. Law and regulation are expected to enable innovation, while at the same time protecting society from unintended consequences. However, assessing new technological risks confronts deep uncertainty and limited knowledge. In contrast to simple risks (e.g. car accidents), technological risks (such as risks stemming from new health technologies, nanotechnology, biotechnology, or robotics as discussed in this special issue) cannot be calculated according to traditional technocratic models, namely as a statistically foreseeable function of probability and effects. It is widely recognised that regulating new and emerging technologies is challenging for law due to problems of uncertainty and limited knowledge in the assessment and management of technological risks. To address this challenge it is crucial to study the ways in which law and regulation can successfully respond and adapt to technological progress.